ENT 530 Social Media Portfolio: Kerepeking / Norfadzlina Zakaria - Zakaria, Norfadzlina (2021)
KerepeKing is a local business that sells Kerepek Ubi Kayu or also known as tapioca chips. The specialty about KerepeKing is the taste of the products where it is using the traditional family recipe and it is still the same even years has passed. All products at KerepeKing are sold at an affordable price. Initially, KerepeKing started as an offline based business in 2019. However, along with the opportunity to conduct this assignment, I see the potential to expand the market of KerepeKing and decided to incorporate into an online business. Before this, KerepeKing marketed its product to the small retailer nearby. The target market of KerepeKing is huge, which people regardless the gender or age can enjoy the products. Therefore, I believed that products offered by KerepeKing is marketable. Therefore, a Facebook Page named KerepeKing was created for this business. Through that platform, business can engage with many people that will become the potential customers. I’ve promoted KerepeKing in the page by posting teaser post. In order to attract many customers, I’ve further promoted the products through the copywriting technique which consist of soft sell and hard sell. After being in the online base for almost six months, KerepeKing products has being sold for more than 300 packs and was able to generate nearly 4 digit sales within this period.